Theoretical Trends on Classification of Units of Phraseology - Atajonova, Maloxat (The Lingua Spectrum, 2024)
This thesis analyzes the issues related to the theoretical trends on classification of phraseological units. Phraseological units are an essential component of literary works, encompassing their spiritual, cultural, and aesthetic layers. The accurate representation and alignment of phraseological units in translation are crucial for saving the complete meaning the original text.